Ocular Decompression Retinopathy : A Case Series - Singh, Kirti; Bhattacharyya, Mainak; Wali, Keerti; Rana, Kartik; Jain, Divya (Nepalese Journal of Ophthalmology, 2018)
Introduction: Ocular decompression retinopathy (ODR) is a relatively rare entity with variable prognosis depending on extent and pre-existing condition. This article describes profile of two cases with a brief review of the condition. Case report: Case 1 highlights extensive choroidal detachment with subhyaloid haemorrhage and multiple intra-retinal hemorrhages in the posterior pole seen on first post-operative day in a 6 year old child with congenital glaucoma who underwent Trab & Trab. Case 2 describes multiple intraretinal hemorrhages seen at posterior pole on second post-operative day in a 24 year old pregnant lady with post traumatic cataract and secondary glaucoma who underwent cataract extraction with Cionni ring. Both patients had complete resolution of the haemorrhages with topical steroids. Conclusion: Ocular decompression retinopathy is mostly seen after operations on cases with advanced glaucoma and those with vulnerable blood flow fluidics. Adequate precautions to prevent this entity should be adopted during surgery and management of the manifest entity is conservative with good prognosis.